Methodological Mistakes and Econometric Consequences - Asad Zaman (International Econometric Review (IER), 2012)
Econometric Methodology is based on logical positivist principles. Since logical positivism has collapsed, it is necessary to re-think these foundations. We show that positivist methodology has led econometricians to a meaningless search for patterns in the data. An alternative methodology which relates observed patterns to real causal structures is proposed.
Keywords: C18; B40; 330; Econometric Methodology; logical positivism; realism; causality; VAR models; Forecasting; surprise; goodness of fit